Ultrasound‐Assisted Extraction of Water‐Soluble Polysaccharides from the Fruit of Acanthopanaxbrachypus: Physicochemical, Structural and Functional Properties. Issue 6 (5th May 2021) - Hu, Haobin; Liang, Haipeng; Wang, Yufeng; Yuan, Runan; Sun, Jiao; Zhang, Lala; Lu, Yani
Abstract: The ultrasound‐assisted extraction (UAE) parameters of total water‐soluble polysaccharides (TABPs) from Acanthopanaxbrachypus fruit were optimized by Box‐Behnken design (BBD) and response surface methodology (RSM). Physicochemical, structural, and functional properties of TABPs were investigated by chemical analysis, inductively coupled plasma optical emission spectrometry (ICP‐OES), high performance liquid chromatography (HPLC), scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FT‐IR), thermogravimetric analysis (TGA), water‐holding capacity (WHC), oil‐holding capacity (OHC), emulsion capacity (EC), emulsion stability (ES), as well as DPPH . and ABTS .+ scavenging assays. The results showed that the maximal UAE‐yield of TABPs was 3.81±0.18 % under the optimal conditions (ultrasonic power 325 W, extraction temperature 47 °C, extraction time 22 min). TABPs was rich in some beneficial element (Mg, K, Fe, Zn and Na) but little in harmful elements (Hg, Cd, As and Pb), and displayed rough surface with flake‐like features and large dents, contained 93.89±0.08 % of total carbohydrate with more different monosaccharides including glucose, galactose, rhamnose, arabinose, mannose, xylose, and uronic acid in a molar ratio of 8.83 : 7.90 : 4.74 : 4.55 : 2.80 : 2.39 : 1.00, respectively. TABPs exhibited broad weight distribution (11.2–133.5 kDa), excellent thermal stability (>280 °C), WHC (0.61±0.08 g water/g sample) and OHC (4.53±0.12 g oil/g sample), as well as higher EC (43.75±1.23 %) and ES (38.32±1.50 %). Furthermore, TABPs also displayed remarkable scavenging activities on DPPH . and ABTS .+ in vitro . These findings provide a scientific basis for the applications of TABPs in functional additives for food, medicine, and cosmetics. Abstract :